2017
DOI: 10.1371/journal.pone.0177025
|View full text |Cite
|
Sign up to set email alerts
|

Beyond causes of death: The social determinants of mortality among children aged 1-59 months in Nigeria from 2009 to 2013

Abstract: BackgroundMillions of children worldwide suffer and die from conditions for which effective interventions exist. While there is ample evidence regarding these diseases, there is a dearth of information on the social factors associated with child mortality.MethodsThe 2014 Verbal and Social Autopsy Study was conducted based on a nationally representative sample of 3,254 deaths that occurred in children under the age of five and were reported on the birth history component of the 2013 Nigerian Demographic and Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…A preliminary list of variables available in the survey was created based on previous studies of associations with childhood mortality [ 15 , 17 , 34 , 37 40 , 42 46 , 56 , 57 ]. Cox regression models with clustering at the household level were used to estimate the effects of independent variables on survival with effects given as hazards ratios.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary list of variables available in the survey was created based on previous studies of associations with childhood mortality [ 15 , 17 , 34 , 37 40 , 42 46 , 56 , 57 ]. Cox regression models with clustering at the household level were used to estimate the effects of independent variables on survival with effects given as hazards ratios.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the focus of the MDGs on national data ignored these within-country inequities [ 9 , 11 13 ], and that increased health spending often benefits those that were best off to start [ 11 , 12 , 14 ]. These subnational differences within countries highlight the need for local data to inform health services implementation efforts [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, VASA, an integrated approach, whereby VA is merged with SA to identify not only the medical causes of mortalities but also to identify the social contributors of child deaths. This integrated tool is under trial in some of the low resource settings across the globe (4,(6)(7)(8)(9). Literature suggests that CHERG (Child Health Epidemiology Reference Group) VASA integrated tool, which is based on the so-far most holistic conceptual framework, i.e., "The Pathway to Survival Conceptual Framework" (TPtoSCF) (10), have been utilized in several countries (6,7,9,11) for exploring the most relevant medical and social determinants of mortality events.…”
Section: Introductionmentioning
confidence: 99%
“…The CF ultimately assists in developing new interventions and focusing the existing ones (in the presence of more explicit evidence) towards preventing child mortalities and ultimately has strong policy implications in child survival4. Global literature suggests evidence in support of using TPtoSCF for understanding the complete range of social determinants linked with child death events [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…This approach can give extended data on most relevant biological and social determinants related to specific death event and ultimately help in assigning a broader cause of death. However, the literature shows that such investigations have been undertaken by either way; administering VA and SA tools separately (but in synergy) for each death event [28][29][30][31] or using an integrated tool where SA is merged with VA, thereby making a single tool for recording data on biological and social determinants 8, [21][22][23][24][25][26][32][33][34][35] . However, logically, the single integrated tool should be based on an integrated CF that should be holistic in recording biological and social determinants of child mortality.…”
Section: Introductionmentioning
confidence: 99%